Temporal Trends Of Pharmacologic Therapies For Patients With Chronic Obstructive Pulmonary Disease In Alberta, Canada - Tran DT; Akpinar I; Mayers I; Makhinova T; Jacobs P (International Journal of COPD, 2019)
Dat T Tran,1,2 Ilke Akpinar,1 Irvin Mayers,3 Tatiana Makhinova,2 Philip Jacobs3 1Institute of Health Economics, Edmonton, Alberta, Canada; 2Faculty of Pharmacy and Pharmaceutical Sciences, University of Alberta, Edmonton, Alberta, Canada; 3Faculty of Medicine, University of Alberta, Edmonton, Alberta, CanadaCorrespondence: Dat T TranInstitute of Health Economics, #1200 – 10405 Jasper Avenue, Edmonton, Alberta T5J 3N4, CanadaTel +1 780 448 4881Fax +1 780 448 0018Email dttran@ualberta.caObjectives: To describe the trends in pharmacologic treatment for patients newly diagnosed with chronic obstructive pulmonary disease (COPD) in Alberta, Canada.Methods: We linked Alberta health databases to identify patients aged ≥35 years with incident COPD between April 2010 and March 2017. Incident cases were defined as those who did not have a hospitalization or outpatient visit with COPD in the previous 2 years. Patients were categorized into two groups: 1) incident cases at a hospital and 2) incident cases at an outpatient clinic, and both were followed until death or being censored by 31 March 2018. Utilization of COPD medication for 30 days following incident event and adherence in maintenance therapy over time were reported.Results: The study included 33,169 patients with incident COPD (hospital: 9,089; outpatient: 24,080). In 18,666 (56.3%) patients starting medication within 30 days of the incident event (2010: 52.7%; 2016: 56.6%; p=0.002), SABA (60.5%) and LABA/ICS (41.6%) were most commonly used. ICS (without LABA) was used in 14.2% and was used as monotherapy in 4.5% of patients. The proportion of patients who initiated any ICS was similar (hospital: 56.7%; outpatient: 55.7%; p=0.194) and decreased in both settings over time (p<0.001). Drug adherence during the first year after the incident event was 54.3%, higher among hospital patients (66.5% vs 48.9%; p<0.001), and improved over time (2010: 53.4%; 2016: 57.4%; p<0.001).Conclusion: The initiation of and adherence to pharmacologic therapy for patients with COPD is low but improves over time. While SABA and LABA/ICS are most commonly used, ICS utilization decreases over time.Keywords: COPD, drug utilization, pharmacologic therapy, Canada